No time out: mobility, rhythmicity and urban patrol in the twenty‐four hour city. (26th August 2013) - Smith, Robin James; Hall, Tom
Abstract: This paper is about the twenty‐four hour city and analyses this phenomenon with the assistance of a case study dispersed across (temporally and spatially) twenty‐four hours spent moving in, around and with the city centre of Cardiff, UK. Reporting from a continuous twenty‐four hour period of fieldwork the paper describes the round‐the‐clock work of a range of urban patrols – street sweepers, Police Community Support Officers and outreach workers – who, in various ways, contribute to the maintenance of the social and physical fabric of the city centre. Describing the seemingly disparate activities of these patrols, we make an argument for an attention to the polychronic mobility practices in and through which the street‐level politics of space, movement and time are produced and negotiated. Indeed, the circulations of these patrols throws up a supporting cast of vulnerable street‐populations – the homeless, street drinkers and street‐based sex workers. Here, then, we juxtapose our description of this quotidian city with the imagery and politics of the '24‐Hour City' in pointing to a nuanced (rather than adversarial) and mobile (rather than static) relationship between need and vulnerability and the management of space, time and mobility in the city centre.